The Use of Once-Daily Dosing of Gentamicin in Obstetrics and Gynecology. Issue 4 (1998) - Wiesenfeld, H. C.; Heine, R. P.
Abstract : Gentamicin is a widely-used antimicrobial agent for obstetric and gynecologic infections. Renewed excitement in this antibiotic has arisen from recent information supporting less frequent dosing. In this symposium, we will describe the pharmacokinetics of gentamicin and review new information advocating the use of once-daily administration of gentamicin.